1997
DOI: 10.1046/j.1365-2958.1997.4621825.x
|View full text |Cite
|
Sign up to set email alerts
|

InlB: an invasion protein of Listeria monocytogenes with a novel type of surface association

Abstract: SummaryListeria monocytogenes is an intracellular bacterial pathogen that expresses several surface proteins critical for the infectious process. Such proteins include InlA (internalin) and InlB, involved in bacterial entry into the host cell, and ActA, required for bacterially induced actin-based motility. Although the molecular mechanisms of attachment of InlA and ActA have been characterized, essentially nothing is known about how InlB is anchored to the bacterial surface. Using a genetic approach, we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
292
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 232 publications
(306 citation statements)
references
References 28 publications
12
292
0
2
Order By: Relevance
“…Deletion of this domain impaired adherence to host cells, whereas addition of GW repeats improved the binding to the cell surface. Similarly, the autolysin Ami in L. monocytogenes contains a N-terminal catalytic domain and a Cterminal domain that is homologous to the GW domain in InIB but contains 8 GW modules arranged in tandem (Braun et al, 1997;Milohanic et al, 2001). Similar six to eight tandem repeat motifs have been described in the S. caprae atlC gene product (Alligent et al, 2001) and the surface protective antigen (SpaA) of E. rhusiopathiae (Makino et al, 1998).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Deletion of this domain impaired adherence to host cells, whereas addition of GW repeats improved the binding to the cell surface. Similarly, the autolysin Ami in L. monocytogenes contains a N-terminal catalytic domain and a Cterminal domain that is homologous to the GW domain in InIB but contains 8 GW modules arranged in tandem (Braun et al, 1997;Milohanic et al, 2001). Similar six to eight tandem repeat motifs have been described in the S. caprae atlC gene product (Alligent et al, 2001) and the surface protective antigen (SpaA) of E. rhusiopathiae (Makino et al, 1998).…”
Section: Discussionmentioning
confidence: 78%
“…Although ESTs that contain this motif are in the database, to date no other mammalian proteins with this motif have been reported. A clue to the function of GW repeats may come from studies of bacteria such as Listeria monocytogenes, Staphylococcus caprae, and Erysipelothrix rhusiopathiae, where it has been suggested that proteins bearing these repeats play an important role in anchoring bacterial proteins to the surface of the cell (Makino et al, 1998) and anchoring bacteria to target cells (Braun et al, 1997;Milohanic et al, 2001). The mode of binding is not clearly understood, but is thought to occur via interaction with lipoteichoic acid or with specific cell surface proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of InlB-coated Beads-Coating of latex beads with purified InlB and incubation of host cells with InlB-coated latex beads were performed as previously described (14,20), where 1-m diameter latex beads were coated following the manufacturer's instructions (Molecular Probes). Prior to addition to siRNA-treated HeLa cells, InlB-coated beads were briefly sonicated, diluted in DMEM, and added to HeLa cells at a multiplicity of ϳ100 beads per cell.…”
Section: Methodsmentioning
confidence: 99%
“…Its C-terminal cell wall-anchoring (CWA) domain contains eight glycine-tryptophan (GW) modules, through which Ami associates to the bacterial surface, putatively by interaction with lipoteichoic acids (LTAs). [35][36][37] The CWA domain of Ami has been shown to mediate bacterial adhesion to human epithelial cells. 38,39 In addition, an ami mutant is attenuated in the liver of intravenously infected mice, suggesting a role in L. monocytogenes virulence.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%